2020
DOI: 10.17352/2455-2283.000074
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of children with celiac disease: A single-center experience

Abstract: Background and objectives:The clinical fi ndings of Celiac Disease (CD) change over time. Instead of classical symptoms such as diarrhea, growth retardation, abdominal bloating, atypical symptoms such as chronic constipation and abdominal pain may be the only sign of CD. In this study, we aimed to evaluate the clinical features of our patients with CD. Material and methods: This retrospective study was conducted between March 2017 and January 2019. 61 children with CD were included in the study. Local Ethics C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The mean age of the children is 7.7±3.3 years in our study which is comparable with other local and regional studies 9,14,15 . Data stratification according to gender has shown female preponderance in our study: there was significant relationship between asymptomatic CD and female gender (P value= 0.08).…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of the children is 7.7±3.3 years in our study which is comparable with other local and regional studies 9,14,15 . Data stratification according to gender has shown female preponderance in our study: there was significant relationship between asymptomatic CD and female gender (P value= 0.08).…”
Section: Discussionsupporting
confidence: 91%
“… 7 , 8 An analysis of children with CD found that the presence of Hashimoto thyroiditis, Turner syndrome, Down syndrome, diabetes mellitus, and hypothyroidism all contributed to the possibility of CD in these children. 9 To mitigate the risk of enduring complications, such as malignancy, stunted growth, infertility, and reduced bone density, it is imperative to diagnose CD as early as possible and initiate treatment. 10 , 11 Single‐nucleotide polymorphism (SNP)‐based assays are economical and effective at detecting common variants associated with CD, such as HLA‐DQ7.5, DQ2.2, DQ8, and DQ2.5.…”
Section: Introductionmentioning
confidence: 99%
“… 19 The ratio of affected females to males in CD varies from 1:3 to 1.5:1; this disease is known to affect individuals of all ages, with more than 70% of new diagnoses occurring in individuals over 20 years old. 9 , 20 European nations (such as Finland and Sweden) and people of European ancestry demonstrate an increased susceptibility to developing CD in contrast to other geographic areas. 21 Additionally, The prevalence of CD is different among countries, and it is believed to affect approximately 1% of the overall population in Iran.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations